Why Did Jesus’ Disciples Fail to Cast Out the Deaf and Mute Spirit? (Mark 9:14–29) - Löfstedt, Torsten (Svensk Exegetisk Årsbok, 2023)
On the basis of a close reading of the pericope of the healing of the boy with a mute spirit as it is recorded in Mark 9:14–29, I argue that Mark intended Jesus’ enigmatic answer “this kind can can come out only through prayer and fasting” (Mark 9:29, NRSV) to be a lesson for his readers on how to prepare for exorcisms. Like the disciples who failed to cast out the mute demon while Jesus’ was being transfigured, so too Mark’s readers must prepare for exorcisms by prayer and fasting, for Jesus is not present with them the way he was for his disciples during most of his earthly ministry.